Space and Queer Identity: Vela Gay Bar in Copenhagen as an Example of the Significance of Female-Oriented Space and Queer Community - Rieger, Clara (Culture and History: Student Research Papers, 2025)
This article examines the critical role of queer spaces in shaping queer identity formations, charting a historical progression from essentialist conceptions to more pluralistic understandings. Focusing on how and why queer women claim and engage with space, the analysis draws on a series of ethnographic studies and a semi-structured interview with the owner of Copenhagen’s sole female-oriented venue, Vela Gay Bar. The findings underscore the cultural significance of nighttime leisure spaces in fostering visibility and solidarity. However, contemporary queer women increasingly locate community across broader queer or even within heteronormative spaces, presenting new challenges for maintaining individual identity constructions while expanding community over the borders of queer subgroups.